Aspectos Gramaticais da Língua KA'APOR - Mario Alexandre Garcia Lopes (2009)
This thesis aims at investigating the grammatical aspects of the theKaapor language. I firstly investigate the phonology and the morphology. As for the phonology part, I describe the vowels and the consonants. After this, I focus my attention on the phonemes trying to establish the contexts in which the minimal pairs come up. Then, I look into the complementary distribution and into the free variation of the phones. As for the morphology, I consider the grammatical status of the relational prefixes - {r- 8 Æ-} e {i- 8 h- 8 Æ-} - and examine the verbal morphology.In respect to relational prefixes, I investigate their occurrence in nouns,postpositional phrases, and in stative verbs. Secondly, I analyse three aspects of the morphosyntax. I study the expressions of gradation and quantification. Then I analyze the morphosemantic properties of the clitic [.kE]. I conclude with the investigation of verbal predicates, and suggest four types of alignments: nominative-absolutive, ergative pacient, fluid-S systems, and neutral. In the last part of the thesis, I analyse the order of the main constituents. I specifically analyse the relationship between the noun and its determiners (adjectives, demonstrative pronouns, possessive pronouns, numerals, quantifiers, and the particle [.kE]), and the order in declarative, subordinate and interrogative clauses.In this analysis of the Kaapor language, corpora from Kakumasu (1990;1989; 1986); Corrêa da Silva (1997); Caldas (2001); Silva (2001) were used as well as narratives from documentation of storytelling courses, which were held from July to August 2006, and in January 2008.